Roles de género en el sistema de personaje de Madame Bovary de Gustave Flaubert - Usiña Tana, Madelyn Scarleth (2026)
This research project aimed to analyze gender roles in the characters of Madame Bovary, highlighting the influence of the female role in the narrative and its relationship to 19th-century bourgeois society. It emphasized Flaubert's innovative writing style, which sparked social critique regarding the conception of women both within and outside the family. A qualitative methodology was chosen, and the study was categorized as non-experimental, basic, and descriptive. The object of study was Gustave Flaubert's novel Madame Bovary, selected as the primary unit of analysis. The hermeneutic method and content analysis techniques were also implemented. The analysis of the characters in Madame Bovary revealed how Flaubert's text portrays her environment as a society steeped in social and cultural limitations imposed on 19th-century women, who were expected to abide by established norms and suffer the consequences of defying them. The study concludes that Madame Bovary critically reflects the gender roles of the period. Through Emma, the tension between personal desire and social norms is evident. The novel inherently denounces inequality and shows how the patriarchal system represses female freedom, harshly punishing any attempt at rebellion